Cardioprotective Impact of Aqueous Saussurea lappa Root Extract in Female Rats Treated with Tamoxifen - Eman Ali Faraj Hamouda (Libyan Journal of Medical and Applied Sciences, 2025)
Tamoxifen (TMX), a widely used anti-estrogenic agent for breast and ovarian cancer therapy, has been associated with cardiotoxicity upon long-term administration. Saussurea lappa (Indian Costus root) possesses potent antioxidant and cardioprotective properties in preclinical studies, suggesting its potential in preventing drug-induced cardiac injury. This study investigated the cardioprotective efficacy of Saussurea lappa root extract (SLRE) against TMX-induced cardiotoxicity in vivo. Experimental animals were divided into four groups: control, SLRE-treated (200 mg/kg), TMX-treated (40 mg/kg), and a combination group receiving both agents. All treatments were administered orally over 28 days. Cardiac injury was assessed by measuring serum biomarkers lactate dehydrogenase (LDH), creatine kinase-MB (CK-MB), and troponin I and by histopathological evaluation of myocardial tissue. TMX administration led to significant elevations in cardiac biomarkers and notable histopathological damage, indicative of cardiotoxicity. Co-administration of SLRE markedly reduced LDH, CK-MB, and troponin I levels (P < 0.001) and preserved cardiac tissue architecture. These findings suggest that SLRE mitigates TMX-induced cardiac injury, likely through antioxidant and anti-inflammatory mechanisms. The study highlights the therapeutic potential of SLRE as a natural cardioprotective agent and encourages further investigation into its mechanisms and clinical applications.